PENERAPAN MODEL PEMBELAJARAN PROBLEM BASED LEARING (PBL) UNTUK MENINGKATKAN HASIL BELAAR SISWA KELAS IV SEKOLAH DASAR PADA MATA PELAJARAN MATEMATIKA DI SDN 195 ISOLA - Robby Abdillah; Kurniasih; Resti Saripah Ningsih (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2023)
This research aims to improve the learning outcomes of class IV-A SDN 195 ISOLA in Mathematics through the application of the Problem Based Learning (PBL) learning model. This type of research is Classroom Action Research (PTK) which is carried out in 3 cycles with 3 hours of study for each cycle. Each cycle consists of several stages, namely planning, implementation of action, observation and reflection. The first cycle was carried out to discuss and see the initial abilities of students. The subjects in this study were students of class IV-A at SDN 195 ISOLA consisting of 28 students. The main techniques in data collection were carried out by means of tests and observations, while the supporting techniques used interviews and documentation. The results showed that the application of the Problem Based Learning (PBL) learning model could improve student learning outcomes in class IV-A starting from the pre-action Cycle 1, Cycle I and Cycle III, which was 67.65 in Cycle I, increasing to 75.65 in Cycle II. and again increased to 80.86 in cycle III. The conclusion of this study is that the application of the Problem Based Learning (PBL) learning model can improve the mathematics learning outcomes of class IV-A students.